2007
DOI: 10.1002/art.22570
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anti–Cyclic citrullinated peptide antibody levels with PADI4 haplotypes in early rheumatoid arthritis and with shared epitope alleles in very late rheumatoid arthritis

Abstract: Objective. Anti-cyclic citrullinated peptide (anti-CCP) antibodies are rheumatoid arthritis (RA)-specific serologic markers. RA susceptibility has been associated with HLA-DRB1 shared epitope (SE) alleles and single-nucleotide polymorphism (SNP) haplotypes in the peptidyl arginine deiminase 4 gene (PADI4). This study was undertaken to determine whether anti-CCP levels are associated with PADI4 haplotypes and/or SE alleles in Korean patients with RA.Methods. Three nonsynonymous SNPs in PADI4 (padi4_89, padi4_90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 37 publications
2
37
1
1
Order By: Relevance
“…For example, PTPN22 [6] was reported to have To achieve the optimal correction for multiple testing of single nucleotide polymorphisms (SNPs) in linkage disequilibrium (LD) with each other, the effective number of independent markers in PARP was calculated using the software SNPSpD (http://gump.qimr.edu. au/general/daleN/SNPSpD/) a relationship with RA susceptibility in Caucasians; in contrast, PADI4 has been reported to show relation to RA susceptibility in Asians [4,5]. Another reason for the lack of association between PARP-1 polymorphisms and RA in our study could be the effects of as yet undiscovered functional genetic variants that could potentially interact with PARP-1.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…For example, PTPN22 [6] was reported to have To achieve the optimal correction for multiple testing of single nucleotide polymorphisms (SNPs) in linkage disequilibrium (LD) with each other, the effective number of independent markers in PARP was calculated using the software SNPSpD (http://gump.qimr.edu. au/general/daleN/SNPSpD/) a relationship with RA susceptibility in Caucasians; in contrast, PADI4 has been reported to show relation to RA susceptibility in Asians [4,5]. Another reason for the lack of association between PARP-1 polymorphisms and RA in our study could be the effects of as yet undiscovered functional genetic variants that could potentially interact with PARP-1.…”
Section: Discussioncontrasting
confidence: 78%
“…The human leukocyte antigen (HLA) complex gene on chromosome 6 has been shown to be a major contributor to RA pathogenesis [1], and several contributing non-HLA genes have also been reported [2]. Non-HLA genes known to be associated with RA susceptibility include but are not limited to PADI4 [3][4][5], PTPN22 [6], TRAF1-C5 [7,8], STAT4 [9,10], and 6q23/TNFAIP3 [11].…”
Section: Introductionmentioning
confidence: 97%
“…PADI4 is a compelling candidate gene, because it encodes one of the enzymes responsible for citrullination of endogenous proteins, and an antibody response to citrullinated peptides is highly specific for RA (21). Numerous studies in Asian populations have demonstrated the association of PADI4 with RA (10,(22)(23)(24)(25), but these associations are either absent or very weak in populations of European ancestry (13,14). It is possible that this difference reflects an interaction of PADI4 genetic susceptibility with environmental factors, because citrullination may also be related to smoking or other environmental exposures (1,2,26).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of statistical power because of the small sample size is likely the cause of these negative findings; associations between these genes and anti-CCP have in fact been found in larger cohorts 10,11 .…”
Section: Journal Of Rheumatologymentioning
confidence: 99%